Apolipoprotein M/sphingosine-1-phosphate: novel effects on lipids, inflammation and kidney biology. Issue 3 (June 2019) - Bisgaard, Line S.; Christoffersen, Christina
Abstract : Purpose of review: In 2011, the crystal structure of apolipoprotein M (apoM) and its capacity to bind sphingosine-1-phosphate (S1P) was characterized. Since then, a variety of studies has increased our knowledge on apoM biology and functionality. From being an unknown and hardly significant player in overall metabolism, apoM has gained significant interest. Recent findings: Key discoveries in the last 2 years have indicated that the apoM/S1P complex has important roles in lipid metabolism (affecting triglyceride turnover), inflammation (a marker of severe sepsis and potentially providing anti-inflammatory signaling) and kidney biology (potential to protect against immunoglobulin A nephropathy). Summary: Several studies suggest a potential for apoM/S1P as biomarkers for inflammation, sepsis and nephropathy. Also, a novel chaperone is characterized and could have potential as a drug for treatment in inflammation and nephropathy.